2011
DOI: 10.1136/ard.2011.154799
|View full text |Cite
|
Sign up to set email alerts
|

Golimumab administered subcutaneously every 4 weeks in ankylosing spondylitis: 104-week results of the GO-RAISE study

Abstract: ObjectiveTo assess the efficacy and safety of golimumab over 104 weeks in patients with active ankylosing spondylitis.MethodsAt baseline, patients with active ankylosing spondylitis (n=356) were randomly assigned (1:1.8:1.8) to subcutaneous injections of placebo (group 1), golimumab 50 mg (group 2) or golimumab 100 mg (group 3) every 4 weeks. At week 16, patients in groups 1 and 2 with <20% improvement in total back pain and morning stiffness entered early escape to 50 or 100 mg, respectively. At week 24, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 20 publications
10
76
0
8
Order By: Relevance
“…No further ethical approval was required to conduct the additional data analyses reported herein. Patient entrance criteria and study designs for each trial have been reported [8][9][10][11][12][13][14][15][16][17]18,19,20,21,22,23,24 and are summarized in Table 1. Additionally, further details of each trial are available at clinicaltrials.gov (GO-BEFORE: NCT00264537, GO-FORWARD: NCT00264550, GO-AFTER: NCT00299546, GO-REVEAL: NCT00265096, GO-RAISE: NCT00265083).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No further ethical approval was required to conduct the additional data analyses reported herein. Patient entrance criteria and study designs for each trial have been reported [8][9][10][11][12][13][14][15][16][17]18,19,20,21,22,23,24 and are summarized in Table 1. Additionally, further details of each trial are available at clinicaltrials.gov (GO-BEFORE: NCT00264537, GO-FORWARD: NCT00264550, GO-AFTER: NCT00299546, GO-REVEAL: NCT00265096, GO-RAISE: NCT00265083).…”
Section: Methodsmentioning
confidence: 99%
“…Our current study was a pooled analysis of previously collected safety data from 5 large multicenter trials [8][9][10][11][12][13][14][15][16][17]18,19,20,21,22,23,24 , each of which was conducted according to the Declaration of Helsinki and the International Committee on Harmonisation Good Clinical Practices. Each of the phase 3 study protocols was approved by central or individual site institutional review boards/ethics committees, and all patients provided written informed consent prior to any study-related procedures.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Golimumab (GLM) is a novel fully human anti-TNF monoclonal antibody, recently approved for a variety of rheumatic conditions, [3][4][5] with very promising results. Herein we describe a case that exemplifies the efficacy of GLM in a patient with refractory Behçet uveitis, and represents, to our knowledge, the first report about the use of GLM in Behçet uveitis.…”
Section: Dear Editormentioning
confidence: 99%
“…Biological therapy with TNF antagonists has created new possibilities to control this condition, particularly in those patients refractory to conventional immunosuppressive agents. 8 GLM is a recent development in TNF antagonism and has been recently approved for the treatment of a variety of rheumatic inflammatory conditions, [3][4][5] with an acceptable safety profile, and remains the only TNF antagonist that has shown efficacy in patients refractory to other anti-TNF agents. 9 Due to GLM molecular structure, a fully human monoclonal antibody, GLM has a lower probability of developing neutralizing antibodies compared to other anti-TNF such as IFX, a chimeric monoclonal antibody, decreasing the risk of an allergic infusion reaction and any loss of efficacy.…”
Section: Case Reportmentioning
confidence: 99%
“…All patients provided written informed consent. The GO-RAISE patient selection criteria and study design have been described elsewhere 14,15 . Patients had definite AS according to the modified New York criteria 16 , and active disease defined as a Bath Ankylosing Spondylitis Disease Activity Index 17 score ≥ 4 and a total back pain visual analog scale score ≥ 4.…”
Section: Rheumatologymentioning
confidence: 99%